2002
DOI: 10.1002/dmrr.297
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing coronary artery disease in diabetic patients

Abstract: Although several diagnostic modalities are available to the clinician interested in diagnosing coronary artery disease, very few have been validated in diabetic populations. This review discusses the non-invasive diagnosis of coronary disease in diabetic patients. Evidence regarding the prevalence and prognostic significance of silent ischemia is reviewed and the potential impact of silent ischemia on the diagnostic characteristics of the exercise treadmill test discussed. Other diagnostic tools are considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
0
5
1
Order By: Relevance
“…Indeed, our patients were not population based, but rather selected, so that silent CAD prevalence was about 50%. In a more realistic situation with a silent CAD prevalence of about 10% to 30%, 8 the positive predictive value may be lower than that found in the present study. Nevertheless, the predictive power of the IIEF-5 questionnaire could be increased when used together with other recognized cardiovascular risk factors.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Indeed, our patients were not population based, but rather selected, so that silent CAD prevalence was about 50%. In a more realistic situation with a silent CAD prevalence of about 10% to 30%, 8 the positive predictive value may be lower than that found in the present study. Nevertheless, the predictive power of the IIEF-5 questionnaire could be increased when used together with other recognized cardiovascular risk factors.…”
Section: Discussioncontrasting
confidence: 89%
“…1,2,4 -6 An association between overt coronary artery disease (CAD) and ED has been described. 2,5,6 In the diabetic population, the prevalence of silent CAD is particularly high 7,8 ; nevertheless, at the present, the prevalence of ED among diabetic subjects with asymptomatic CAD is unknown. Silent CAD is a strong predictor of coronary events and early death, especially in diabetic patients.…”
mentioning
confidence: 99%
“…Although IGT and IFG are not considered to be “diseases,” they are associated with increased risk of development of overt diabetes mellitus [14], a true risk factor for morbidity, and mortality from CVDs [15]. However, the association between glucose status and the risk of CVDs starts below the diagnostic threshold for diabetes mellitus [6].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found that the elderly and those with diabetes have higher rates of silent ischemia [15]. Likewise, patients with CKD have been shown to have higher rates of silent ischemia that cluster with serious arrhythmias and other cardiac events [16].…”
Section: Diagnosis Of Acute Coronary Syndrome In Patients With Chronimentioning
confidence: 98%